2017
DOI: 10.1016/j.renene.2017.02.072
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic rating of overhead transmission lines over complex terrain using a large-eddy simulation paradigm

Abstract: Dynamic Line Rating (DLR) enables rating of power line conductors using realtime weather conditions. Conductors are typically operated based on a conservative static rating that assumes worst case weather conditions to avoid line sagging to unsafe levels. Static ratings can cause unnecessary congestion on transmission lines. To address this potential issue, a simulation-based dynamic line rating approach is applied to an area with moderately complex terrain. A micro-scale wind solver-accelerated on multiple gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…While Bao et al 2018did not apply eddy-viscosity reconstruction in their original WRF implementation of VR-IB, the present VR-IB implementation applies this reconstruction. A hybrid RANS/LES scheme proposed by Senocak et al (2007) has been used with VR-IB (Senocak et al 2004;Phillips et al 2017;DeLeon et al 2018), and is therefore included as an option here as well. The hybrid scheme works by blending the grid length scale in Eq.…”
Section: B Immersed Boundary Methods With Logarithmic-law Velocity Rementioning
confidence: 99%
See 3 more Smart Citations
“…While Bao et al 2018did not apply eddy-viscosity reconstruction in their original WRF implementation of VR-IB, the present VR-IB implementation applies this reconstruction. A hybrid RANS/LES scheme proposed by Senocak et al (2007) has been used with VR-IB (Senocak et al 2004;Phillips et al 2017;DeLeon et al 2018), and is therefore included as an option here as well. The hybrid scheme works by blending the grid length scale in Eq.…”
Section: B Immersed Boundary Methods With Logarithmic-law Velocity Rementioning
confidence: 99%
“…Although Bao et al (2018) demonstrated good performance of VR-IB for flat terrain with 30 m horizontal grid spacing, such coarse resolution was not used for a case with more complex terrain. Additionally, Phillips et al (2017) used VR-IB to study flow over complex terrain with horizontal and vertical grid spacings of approximately 30 and 4 m, respectively, for the purpose of improving the rating of power lines. However, there is evidence of poorer performance when coarser grids are used with IB methods (see discussion in Chow et al 2019).…”
Section: A Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…The temperature and thermal rating may be different in each span due to different atmospheric conditions although the same current loading flows through the lines. The line rating of the conductor was calculated by using available standards and applying real-time data in [67], [68]. The line rating of the conductor is dependent on weather conditions in specific circumstances.…”
Section: Transmission Line Thermal Ratingmentioning
confidence: 99%